2006
DOI: 10.1111/j.1464-5491.2006.01988.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced insulin secretion in normoglycaemic patients with β‐thalassaemia major

Abstract: These results support the concept that impaired B-cell function, as reflected by a reduction in the insulin secretion index, is present in beta-thalassaemic patients with normoglycaemia before changes in oral glucose tolerance tests are apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Moreover, insulin signaling in muscle is comparable to ϩ/b controls. These features were unexpected based on previous studies reporting impaired glucose metabolism in iron-loaded patients and animals (1,10,18,41). However, results from such studies have been inconsistent (2,15,23,38).…”
mentioning
confidence: 66%
“…Moreover, insulin signaling in muscle is comparable to ϩ/b controls. These features were unexpected based on previous studies reporting impaired glucose metabolism in iron-loaded patients and animals (1,10,18,41). However, results from such studies have been inconsistent (2,15,23,38).…”
mentioning
confidence: 66%
“…Both insulin secretion capacity (HOMA-B) and insulin sensitivity (HOMA-IR) are known to be impaired in thalassemia major, even in apparently normoglycemic cases. 12 It is important, therefore, to correlate these pre-diabetic biochemical abnormalities with MRI studies. Our results showed that hemosiderosis of the pancreas, as measured by MRI T2*, could not be predicted by age or ferritin levels.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies report that a defect in β-cell insulin secretion (defective insulin secretion) resulting from toxic effects of iron deposition in the pancreas may precede the development of glucose intolerance [25,26] (Figure 2).…”
Section: Figure 2 Iron Load and Glycemic Abnormalities In Thalassemimentioning
confidence: 96%